Notification of crop varieties and registration of germplasm : Variety DBW93 - Singh, S.K. (The Indian Journal of Genetics and Plant Breeding, 2016)
Wheat is one of the major rabi crop in the peninsular zone of Indian wheat belt comprising Maharashtra and Karnataka states where wheat is grown in warmer climatic conditions due to limited water availability and higher temperatures during crop period. Under these conditions, wheat is exposed to early and terminal heat stress conditions and limited water availability as major abiotic factors. The brown and black rusts are also crucial biotic stresses that affect wheat yields.